First Description of Colistin and Tigecycline-Resistant Acinetobacter baumannii Producing KPC-3 Carbapenemase in Portugal - Cátia Caneiras; Filipa Calisto; Gabriela Jorge da Silva; Luis Lito; José Melo-Cristino; Aida Duarte (MDPI AG, 2018)
Herein, we describe a case report of carbapenem-resistant Acinetobacter baumannii and Klebsiella pneumoniae isolates that were identified from the same patient at a Tertiary University Hospital Centre in Portugal. Antimicrobial susceptibility and the molecular characterization of resistance and virulence determinants were performed. PCR screening identified the presence of the resistance genes blaKPC-3, blaTEM-1 and blaSHV-1 in both isolates. The KPC-3 K. pneumoniae isolate belonged to the ST-14 high risk clone and accumulated an uncommon resistance and virulence profile additional to a horizontal dissemination capacity. In conclusion, the molecular screening led to the first identification of the A. baumannii KPC-3 producer in Portugal with a full antimicrobial resistance profile including tigecycline and colistin.